Strategi Gen Z Dalam Menghadapi Perubahan Dunia Kerja dan Pengaruhnya Terhadap Kinerja - Manurung, Elisabeth Jessika; Simamora, Jesika Melina; Yusmalinda, Yusmalinda (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Technological advancements and globalization have brought significant transformations to the workplace, creating challenges for Generation Z as they enter the professional world. This generation is known for its unique characteristics, such as a tendency to use digital technology, a preference for work flexibility, and different communication patterns compared to previous generations. This study aims to analyze the strategies employed by Generation Z in facing workplace dynamics and evaluate their impact on performance. The research uses a quantitative approach with a causal associative method. Data was collected through questionnaires distributed to 40 respondents from various job sectors who fall into the Generation Z category and have at least one year of work experience. The data obtained were analyzed using simple linear regression to measure the relationship between adaptation strategies and individual performance. The results show that Generation Z implements several key strategies in dealing with changes in the workplace, such as utilizing digital technology, flexibility in work patterns, skill development through online courses, and building professional networks through social media. Based on statistical analysis, these strategies are proven to have a positive and significant influence on Generation Z's performance, with a correlation value (R = 0.741) and coefficient of determination (R² = 0.550), indicating that 55% of their performance variability can be explained by the adaptation strategies used. The conclusion of this study affirms that Generation Z has a high adaptability to changes in the workplace, especially in leveraging technology and work flexibility. However, they also face several challenges, such as high work pressure and difficulties in cross-generational communication. Therefore, companies are advised to provide a more flexible work environment and technology-based training programs to support the professional development of Generation Z.